Operando generated ordered heterogeneous catalyst for the selective conversion of CO2 to methanol - Cherevotan, Arjun; Raj, Jithu; Dheer, Lakshay; Roy, Soumyabrata; Sarkar, Shreya; Das, Risov; Vinod, Chathakudath P.; Xu, Shaojun; Wells, Peter; Waghmare, V, Umesh; Peter, Sebastian C. (ACS Energy Letters, 2021)
The discovery of new materials for efficient transformation of carbon dioxide (CO2) into desired fuel can revolutionize large-scale renewable energy storage and mitigate environmental damage due to carbon emissions. In this work, we discovered an operando generated stable Ni-In kinetic phase that selectively converts CO2 to methanol (CTM) at low pressure compared to the state-of-the-art materials. The catalytic nature of a well-known methanation catalyst, nickel, has been tuned with the introduction of inactive indium, which enhances the CTM process. The remarkable change in the mechanistic pathways toward methanol production has been mapped by operando diffuse reflectance infrared Fourier transform spectroscopy analysis, corroborated by first-principles calculations. The ordered arrangement and pronounced electronegativity difference between metals are attributed to the complete shift in mechanism. The approach and findings of this work provide a unique advance toward the next-generation catalyst discovery for going beyond the state-of-the-art in CO2 reduction technologies.

Structure-tailored surface oxide on Cu-Ga intermetallics enhances CO2 reduction selectivity to methanol at ultralow potential - Bagchi, Debabrata; Raj, Jithu; Singh, Ashutosh Kumar; Cherevotan, Arjun; Roy, Soumyabrata; Manoj, Kaja Sai; Vinod, C. P.; Peter, Sebastian C. (Advanced Materials, 2022)
Electrochemical CO2 reduction reaction (eCO(2)RR) is performed on two intermetallic compounds formed by copper and gallium metals (CuGa2 and Cu9Ga4). Among them, CuGa2 selectively converts CO2 to methanol with remarkable Faradaic efficiency of 77.26% at an extremely low potential of -0.3 V vs RHE. The high performance of CuGa2 compared to Cu9Ga4 is driven by its unique 2D structure, which retains surface and subsurface oxide species (Ga2O3) even in the reduction atmosphere. The Ga2O3 species is mapped by X-ray photoelectron spectroscopy (XPS) and X-ray absorption fine structure (XAFS) techniques and electrochemical measurements. The eCO(2)RR selectivity to methanol are decreased at higher potential due to the lattice expansion caused by the reduction of the Ga2O3, which is probed by in situ XAFS, quasi in situ powder X-ray diffraction, and ex situ XPS measurements. The mechanism of the formation of methanol is visualized by in situ infrared (IR) spectroscopy and the source of the carbon of methanol at the molecular level is confirmed from the isotope-labeling experiments in presence of (CO2)-C-13. Finally, to minimize the mass transport limitations and improve the overall eCO(2)RR performance, a poly(tetrafluoroethylene)-based gas diffusion electrode is used in the flow cell configuration.
Keywords: (2) reduction; CO; Electrochemistry; Methanol

Unraveling the cooperative mechanisms in ultralow copper-loaded WC@NGC for enhanced CO2 electroreduction to acetic acid - Bagchi, Debabrata; Riyaz, Mohd; Raj, Jithu; Roy, Soumyabrata; Singh, Ashutosh Kumar; Cherevotan, Arjun; Vinod, Chathakudath P.; Peter, Sebastian C. (Chemistry of Materials, 2024)
Electrochemical CO2 reduction reaction (eCO(2)RR) has been explored on tungsten carbide (WC) nanoparticles embedded on N-doped graphitic carbon (NGC), demonstrating excellent activity toward the formation of acetic acid at an extremely lower potential. The activity has been further enhanced by loading ultralow copper sites into the catalyst system, exhibiting 80.02% Faradaic efficiency (FE) toward acetic acid at an applied potential of -0.3 V (vs RHE). Potential-dependent in situ infrared (IR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, ex situ extended X-ray absorption fine structure (EXAFS) studies, and computational analysis confirm that synergy between uniformly dispersed Cu atoms and WC lattice plays a crucial role in the formation of acetic acid with high FE at a lower potential. It has been observed that the W atom of WC strongly chemisorbs CO2 with a significant change in the C-O bond length and the O-C-O bond angle, in contrast to weaker adsorption on Cu-based catalyst surfaces. The presence of a Cu site enhances the adsorption of CO2, thereby increasing the possibility of C-C coupling kinetically. Most importantly, hydrogen evolution predominates on the catalyst's surface at higher applied potentials (-0.5 to -1.1 V vs RHE), elucidating the mechanism underlying enhanced charge transfer between copper and WC, a phenomenon ascertained through in situ IR spectroscopy and ex situ XPS analysis

Metal deficiency tuned charge transfer in intermetallic Ni2-xSn (x =0.37-0.65) enhances selective conversion of furfural to furfuryl alcohol towards the theoretical limit - Cherevotan, Arjun; Singh, Ashutosh Kumar; Yadav, Anish; Maligal-Ganesh, Raghu V.; Raj, Jithu; Pulparambil, Anu; Goud, Devender; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2025)
Heterogeneous catalysis facilitated by intermetallic nanoparticles has recently been the subject of increased scrutiny, given the enhanced selectivity and stability they bestow on many chemical reactions compared to their monometallic components. This paper explores a series of Ni-Sn (Ni2-xSn, where x = 0.65, 0.5, 0.37) intermetallic compounds supported on a high-surface-area support, SBA-15, as catalysts for the selective hydrogenation of furfural to furfuryl alcohol. Rietveld refinements of the X-ray diffraction data show catalysts with mixed intermetallic phases that assist in the catalysis. At the same time, X-ray photoelectron spectroscopy (XPS) studies and X-ray absorption studies indicate the role played by charge transfer from Sn to Ni for the catalysis. Selectivity to the desired furfuryl alcohol in all the intermetallic samples was high (>97%), but Ni1.35Sn had a relatively lower conversion than the other intermetallic compounds.